Media Ideologies of Love and Marriage Presented in the Program Wedding at First Sight - Majka-Rostek, Dorota (Media - Culture - Social Communication, 2020)
This article examines the assumptions and character of the popular TV show Wedding at First Sight as an ideological message which presents certain models of marriage and marital relations. Elements of the expertise discourse created in the show, as well as elements of viewers’ discourse, are presented in the context of contemporary changes in intimate relationships. The research method used is a qualitative analysis of posts on an Internet forum dedicated to the TV show Wedding at First Sight. The ideology of love and marriage presented there is a mixture of traditional (e.g. traditional division of gender roles) and modern (e.g. open and steady communication) models. Its fundamental characteristic is the assumption that among one’s primary life goals should be a marriage based on rational choice and romantic love at first sight